Public enterprise management : constraints & autonomy - Patil, S. M. (Sanganbasappa Mallangouda), 1919-; Nigam, Raj Kumar, 1923- (Occasional publications (Documentation Centre for Corporate & Business Policy Research (India)), 1981)
Papers.